The Effectiveness of Problem-Solving-Based Group Counselling to Improve Academic Self-Efficacy among Junior High School Students in Pontianak - Eli Trisnowati; Yenni Rizal; Egga Mawaddah; Uray Herlina; Hendra Sulistiawan; Hendrik (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Adolescents often face academic challenges that require strong self-confidence or self-efficacy; however, many students exhibit low levels of learning self-efficacy. Self-efficacy plays a crucial role in determining students' motivation, perseverance, and academic achievement. This study aimed to examine the effectiveness of group guidance using problem-solving techniques in improving the learning self-efficacy of junior high school students. The research employed a quantitative method with a one-group pretest-posttest design. The subjects consisted of 10 students with low self-efficacy, selected through purposive sampling. The research instrument was a self-efficacy questionnaire, and the data were analyzed using a paired sample t-test. The results showed an increase in the average score from 95.50 (pretest) to 111.80 (posttest), with a t-value of -12.899 (p < 0.05). These findings indicate that group guidance using problem-solving techniques is effective in enhancing students’ confidence in dealing with academic challenges. Further research is needed to explore its long-term impact and effectiveness across different educational levels and cultural contexts. Keywords: group counseling, problem solving, academic self-efficacy, students